Sosialisasi Adaptasi Kebiasaan Baru Pencegahan Covid-19 di Sekolah melalui Video Animasi Manola (Aman di Sekolah dengan Protokol Kesehatan) - Nurul Aini Suria Saputri; Utami Dewi (Poltekkes Kemenkes Surakarta, 2022)
Background: The pandemic of COVID 19 has impacted many fields. Referring to the guidance on the implementation of learning through a joint decree of 4 ministers on the central government's policy towards learning in the new school year during the COVID-19 pandemic, in preparing for face-to-face learning in the education unit. The purpose of this community service activity is to socialize the adaptation of new habits (AKB) for the prevention of COVID-19 in schools through animation media. Methods: The author conducted health education on October 22, 2020, using Manola Animation Video for the residents of State Elementary School 002 Tanjungpinang Timur. The results of the questionnaire were analyzed univariately. Results: Based on the results of the analysis of the questionnaire, as many as 100% or all Teachers participating in the socialization said that the content of the animated video material provided was very useful, and they all shared the video with students through the Whatsapp application. Socialization of habit adaptation in schools through the Manola Animation Video can be accepted and implemented by the citizens of SDN 002 Tanjungpinang Timur. Conclusion: The Manola Animation Video is very good and useful for teachers and students. Furthermore, it is suggested that a special page be created to socialize animated videos to all students in preparation for returning to school during the AKB period.